2013
DOI: 10.1001/jamapediatrics.2013.2259
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Autism Spectrum Disorders in Full- and Half-Siblings and Trends Over Time

Abstract: IMPORTANCE To date, this is the first population-based study to examine the recurrence risk for autism spectrum disorders (ASDs), including time trends, and the first study to consider the ASDs recurrence risk for full- and half-siblings. OBJECTIVES To estimate the relative recurrence risk for ASDs in a Danish population, including recurrence in full- and half-siblings, and to examine time trends in ASDs relative to the recurrence risk. DESIGN, SETTING, AND PARTICIPANTS Population-based cohort study in Den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
109
0
10

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(129 citation statements)
references
References 27 publications
6
109
0
10
Order By: Relevance
“…Recurrence risk is the likelihood that a second child with ASD would be born in a family where a child has already been diagnosed with ASD. No consistent recurrence risk for ASD has been established, and rates have varied from 6 to 19 % (Grønborg et al 2013;Ozonoff et al 2011;Ronemus et al 2014;Rosti et al 2014;Werling and Geschwind 2013).…”
Section: Rates Of Recovery From Asd Are Variedmentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrence risk is the likelihood that a second child with ASD would be born in a family where a child has already been diagnosed with ASD. No consistent recurrence risk for ASD has been established, and rates have varied from 6 to 19 % (Grønborg et al 2013;Ozonoff et al 2011;Ronemus et al 2014;Rosti et al 2014;Werling and Geschwind 2013).…”
Section: Rates Of Recovery From Asd Are Variedmentioning
confidence: 99%
“…An example of varied genetic transmission was reported by Jiang et al (2013), who found multiple varied ASD inheritance patterns in just 16 families: 12 rare X-linked deleterious variants, 7 rare deleterious autosomal-dominant mutations, 13 deleterious missense mutations, and 15 de novo deleterious mutations. Another problem for recurrence rate determination was discovered by Grønborg et al (2013), who found increased ASD risk in maternal half-siblings, indicating that environmental factors unique to the mother's pregnancy history may contribute to ASD recurrence risk.…”
Section: Rates Of Recovery From Asd Are Variedmentioning
confidence: 99%
“…Such "infant sibling" studies are especially important for understanding how autism emerges, because younger siblings of children with ASD are 5 times more likely to be diagnosed with ASD than the general population (Grønborg, Schendel, & Parner, 2013;Ozonoff et al, 2011). There has been a great deal of speculation about the role of brain size in ASD, and some data have suggested that toddlers who are later diagnosed with ASD have larger brains than those who are not (Hazlett et al, 2005(Hazlett et al, , 2012Schumann et al, 2010).…”
Section: Developmental Processes Not Just End Products Are Crucialmentioning
confidence: 99%
“…If multiple children (two or more) are affected, recurrence risk increases to about 33 % or more. Newer data suggest a recurrence risk of 7-19 % when one child is affected, and similar risk of 33 % or more when two or more children in a family are affected [67][68][69]. The ACMG guideline suggests using the lower risk estimates until the newer results have been replicated.…”
Section: Refining Recurrence Risks Within a Familymentioning
confidence: 99%